Роль цитокіногенезу у розвитку гострого ураження легень = Role of cytokinesis in the development of acute lung injury - Mahovsky, Vasyl; Osinchuk, Roksolana; Marushchak, Mariya (Journal of Education, Health and Sport, 2015)
Mahovsky V.P., Osinchuk R.R., Marushchak M.I. Роль цитокіногенезу у розвитку гострого ураження легень = Role of cytokinesis in the development of acute lung injury. Journal of Education, Health and Sport. 2015;5(1):133-138. ISSN 2391-8306. DOI: 10.5281/zenodo.14193 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A133-138 https://pbn.nauka.gov.pl/works/530304 http://dx.doi.org/10.5281/zenodo.14193 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.09.2014. Revised 18.01.2015. Accepted: 21.01.2015. Роль цитокіногенезу у розвитку гострого ураження легень Role of cytokinesis in the development of acute lung injury Маховський В.П., Осінчук Р.Р., Марущак М.І. Mahovsky V.P., Osinchuk R.R., Marushchak M.I. Vasyl Mahovsky m_shvaluk@mail.ru Roksolana Osinchuk roxolana_os@bigmir.net Mariya Marushchak m_shvaluk@mail.ru ДВНЗ «Тернопільський державний медичний університет імені І.Я. Горбачевського МОЗ України» SHEI Ternopil State Medical University named after I.Ya. Gorbachevsky MOH of Ukraine Ключові слова: цитокіни, гостре ураження легень, експеримент. Key words: cytokine, acute lung injury, experiment. Резюме. Метою нашої роботи було оцінити зміни фактору некрозу пухлин-α й інтерлейкіну 1β у сироватці крові та бронхоальвеолярному змиві за умови гострого ураження легень в експерименті. Проведене нами дослідження вказало на хвилеподібні зміни у сироватці крові, тоді як у БАЗ зафіксовано зростання концентрації ФНП-α приблизно у 9 разів протягом всього періоду експерименту (р<0,001). Рівень IL–1β зростав на 74,2 % проти контролю в перші 2 год ГУЛ, через 6 год – на 63,5 % відносно даних 2-ої дослідної групи, через 12 год – на 13,3 % проти результатів 3-ої дослідної групи і на 24 год досліду – на 18,9 % порівняно з попередньої групою. У БАЗ через добу спостереження концентрація IL–1β достовірно збільшилась практично вдвічі, причому відбувалось поступове зростання рівня даного цитокіну впродовж 24 год. Отже, за умови гострого гідрохлоридного ураження легень спостерігається статистично значима взаємозв’язана гіперпродукція прозапальних ФНП-α й IL–1β у бронхоальвеолярному змиві та сироватці крові, що може відігравати важливу роль в ініціації та прогресуванні даної патології внаслідок активації й дегрануляції нейтрофілів та запуску метаболічних каскадних реакцій. Summary. The aim of the study was to evaluate changes in tumor necrosis factor alpha and interleukin-1β in the serum and bronchoalveolar lavage during acute lung injury in the experiment. Our study was indicated undulating changes in serum, while in the BAL it was observed increase of the TNF- α concentration about 9 times during the whole period of the experiment (р<0,001). The level of IL-1β grew by 74,2% compared to control in the first 2 hours of ALI, after 6 hours - by 63,5% relative to the data of the second control group, after 12 hours - by 13,3% against the results of the third experimental group, and after 24 hours - by 18,9% compared to previous group. It was significantly increased the concentration of IL- 1β in the BAL by almost twiceafter 24 hours, and the gradual increase in the level of that cytokine was being observed during 24 hours period. So, during hydrochloric-induced acute lung injury we observed statistically significant interrelated hyperproduction of proinflammatory TNF-α and IL-1β in bronchoalveolar lavage and serum, which can play an important role in the initiation and progression of this pathology as a result of activation and degranulation of neutrophils and launching the cascade of metabolic reactions.